Short-term effects of a multi-disciplinary cardiac rehabilitation programme on psychological well-being, exercise capacity and weight in a sample of obese in-patients with coronary heart disease: A practice-level study - Manzoni, Gian Mauro; Villa, Valentina; Compare, Angelo; Castelnuovo, Gianluca; Nibbio, Ferruccio; Titon, Anna Maria; Molinari, Enrico; Gondoni, Luca Alessandro (Psychology, health & medicine, 2011)
Given that many patients referred to cardiac rehabilitation (CR) are obese, diet therapy, exercise training, nutritional and psychological counselling for both obesity and psychological distress should be included as important components in all CR programmes. In this practice-level, observational study we evaluated the short-term within-group effects of a four-week multi-factorial inpatient CR programme specifically addressed to weight loss, fitness improvement and psychological health increase on 176 obese in-patients with coronary heart disease (CHD). Outcome measures were exercise capacity measured with estimated metabolic equivalents (METs), body mass index (BMI) and psychological well-being (PGWBI). Results show statistically significant improvements in all the PGWBI sub-scales and total score, except in general health (p = 0.393). No moderation effects were found for BMI class, age, diabetes and ejection fraction (EF). METs significantly increased by 30.3% (p < 0.001) and BMI decreased by 1.37 points (p < 0.001). Significant correlations were found between BMI and weight reductions with PGWBI anxiety and total score improvements. This multi-disciplinary CR programme including diet therapy, exercise training and psychological counselling provides indication for short-term within-group effectiveness on functional exercise capacity, BMI and PGWBI in a sample of obese in-patients with CHD. However, controlled studies are needed to corroborate the results we found.